2011
DOI: 10.1097/rli.0b013e3182087b03
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Diffusion-Weighted Imaging With Apparent Diffusion Coefficient Mapping for Treatment Response Assessment in Patients With Diffuse Large B-Cell Lymphoma

Abstract: Whole-body DWI with ADC mapping can show a significant increase in ADC values of residual masses persisting after treatment and may help to assess the treatment response in patients with diffuse large B-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 31 publications
3
52
0
2
Order By: Relevance
“…The results of our study suggest that DWI-MRI is almost equal to 18F-FDG PET/CT for follow-up and therapy response assessment in patients with lymphoma, in accordance with the results of previous smaller-sized studies (13)(14)(15)(16)(17)(18)(19)(20). This is of interest, because only the image pattern, but not the underlying information (i.e., tumor property) assessed is similar between the two techniques: DWI visualizes intercellular space narrowing, and thus, cell density (35); whereas 18F-FDG-PET visualizes glucose metabolism, which in turn has been shown to correlate with cell proliferation (36,37).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of our study suggest that DWI-MRI is almost equal to 18F-FDG PET/CT for follow-up and therapy response assessment in patients with lymphoma, in accordance with the results of previous smaller-sized studies (13)(14)(15)(16)(17)(18)(19)(20). This is of interest, because only the image pattern, but not the underlying information (i.e., tumor property) assessed is similar between the two techniques: DWI visualizes intercellular space narrowing, and thus, cell density (35); whereas 18F-FDG-PET visualizes glucose metabolism, which in turn has been shown to correlate with cell proliferation (36,37).…”
Section: Discussionsupporting
confidence: 92%
“…[13][14][15][16][17][18][19], or a retrospective design (20). In addition, these studies included almost exclusively patients with diffuse large B-cell lymphoma (DLBCL) and Hodgkin lymphoma-there are practically no data for indolent nonHodgkin lymphomas (NHL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, the ADC values significantly increased by 36.9%±13.8% on day 7 after chemotherapy onset for responders. Others have reported that ADC values in diffuse large B-cell lymphoma patients increased significantly after treatment and concluded that change of ADC might help to estimate the treatment response in lymphoma patients (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although FDG PET/CT monitoring of therapy of lymphomas (Hodgkin and diffuse large B cell) has been included in the guidelines [42], more recent studies reported low and maybe suboptimal predictive value [79,80] in early therapy assessment, probably related to therapy schemes different from classic chemotherapy, with higher predictive value in end-therapy evaluation. In this setting, MRI with the addition of fMRI (especially diffusion-weighted imaging) showed excellent and complementary results [81]. Additional advantages to be derived from integrated PET/MRI in the therapy response assessment of lymphomas would be the possibility of differentiating recurrence from thymic rebound by the use of chemical shift MRI [82] and the possibility of using the modality in children, thanks to the reduction of radiation exposure as compared with PET/CT.…”
Section: Therapy Response Assessmentmentioning
confidence: 99%